Tourism, Climate Change and the Missing Worker: Uneven Impacts, Institutions and Response - Tufts, Steven (Climate@Work, 2013)
Analyzes the impact of climate change and climate policy on employment in the tourism industry. --Editor's introduction
Keywords: Canada. Climatic changes; Climatic changes; Economic aspects; Economic aspects. Climatic changes; Government policy